The physics of CO2 transfer during carbonated water injection into oil reservoirs: From non-equilibrium core-scale physics to field-scale implication - Foroozesh, J. (Elsevier B.V., 2018)
CO2 can be dissolved into water to make carbonated water (CW). CW can be injected into oil reservoirs for enhanced oil recovery (EOR) and CO2 sequestration purposes. Carbonated water injection (CWI) technique is a cost-effective CO2 based injection strategy that needs less amount of CO2 as compared to other CO2-EOR techniques. We previously showed that for simulation of CWI coreflood experiments, the kinetics of CO2 transfer between the phases should be considered and we accordingly developed a non-equilibrium based two-phase compositional simulator. We also used the developed simulator to simulate some CWI coreflood experiments. This paper aims to explore the role of mass transfer during simulation of CWI process at field (large)-scale by analysing the data of core-scale simulations. To do so, the results of CWI core-scale simulations obtained from our non-equilibrium based simulator are benchmarked against the results from an equilibrium based simulator and a dimensionless number so-called equilibrium number (Ne) is introduced. It is shown that in a specific range of Ne values, the contact time of the oil and water phases inside the system is large enough that the CO2 can be distributed between the phases based on its equilibrium concentration. Contrary to core-scale simulation, it is concluded that mass transfer kinetics during large-scale simulation of CWI process is not important. Moreover, higher oil recovery factor and CO2 storage are predicted at large-scale (reservoir-scale) as compared to the core-scale's results. The findings of this paper can help to better understand the importance of mass transfer kinetics between the phases in porous media. Â© 2018 Elsevier B.V.